Co‐sensitivity to the incentive properties of palatable food and cocaine in rats; implications for co‐morbid addictions. (17th February 2012) - Levy, AnneMarie; Salamon, Avi; Tucci, Mark; Limebeer, Cheryl L.; Parker, Linda A.; Leri, Francesco
ABSTRACT Several lines of evidence suggest that there may be a shared vulnerability to acquire behaviors motivated by strong incentive stimuli. Non‐food restricted male Sprague‐Dawley rats (n = 78) underwent place conditioning with Oreos, and were subsequently tested on cocaine self‐administration (SA) on fixed and progressive ratios, as well as extinction and reinstatement by cocaine primes and by consumption of Oreos. Although there was a group preference for the Oreo‐paired compartment, at the individual level some rats (69%) displayed a preference and others did not. In cocaine SA, 'preference' rats achieved higher break points on a progressive ratio, and displayed greater responding during extinction and cocaine‐induced reinstatement. Within the context of this study, Oreo‐cocaine cross‐reinstatement was not observed. In a control study, rats (n = 29) conditioned with a less palatable food (rice cakes) also displayed individual differences in place preference, but not on subsequent cocaine tests. These findings indicate that there is a relationship between incentive learning promoted by palatable foods and by cocaine. This supports the hypothesis that co‐morbid food‐drug addictions may result from a shared vulnerability to acquire behaviors motivated by strong incentives.